Kajian stilistika dalam antologi puisi negeri dongeng karya mahasiswa universitas peradaban - Lilis Farkhatin; Wulan Purnama; Cintya Nurika Irma (Universitas Ahmad Dahlan, 2020)
Stylistics is basically the activity of writers using language, especially language that triggers creativity to sort out the use of language. In this research using the study of stylistics in the poetry anthology of